BACTERIAL PURULENT MENINGITIS TREATMENT TACTICS OPTIMIZATION - L. N. Mazankova; D. G. Guseva; G. V. Kryuchkova; Mohsen Abdulhamid Nasr (LLC "Diagnostics and Vaccines", 2015)
A clinical and laboratory surveillance of 59 children with purulent bacterial meningitis (PBM) of various etiologies was carried out. Of them 29 children received Viferon® at dosages according to the age. Viferon was prescribed in addition to basic antibiotic therapy. It was detected that introduction of Viferon® in the treatment strategy for patients with PBM of Hib-and pneumococcal etiology leads to a significant reduction in the duration of the major clinical symptoms, shortened time of sanitation of liquor and it promotes correction of immune disorders displayed by significant reduction in the level of IFN-γi proinflammatory cytokines in cerebrospinal fluid.